New species of Oropezella Collin (Diptera, Hybotidae, Ocydromiinae) from Brazil and Costa Rica, with comments on the relationships among species-groups - Ale-Rocha, Rosaly; Freitas-Silva, Rafael Augusto Pinheiro De (Zootaxa, 2014)
The following sixteen new species of Oropezella from Brazil and Costa Rica are described and illustrated: Oropezella aquila sp. nov., O. arcuata sp. nov., O. bicolor sp. nov., O. bipunctata sp. nov., O. clavata sp. nov., O. costaricensis sp. nov., O. falcata sp. nov., O. flavida sp. nov., O. granulosa sp. nov., O. longifrons sp. nov., O. planti sp. nov., O. plaumanni sp. nov., O. rafaeli sp. nov., O. spathula sp. nov., O. uncata sp. nov. and O. undulata sp. nov. A new combination is proposed: Oropezella amazonica (Rafael & Ale-Rocha, 1990) is transferred from Ocydromia. Additionally, an identification key to all 25 Neotropical and Andean species of Oropezella is provided. A cladistic analysis of Oropezella using 29 species from the Neotropical, Andean, Palearctic and Neozelandic regions is performed and its results and implications discussed.